A late quartet [videorecording (DVD)] - Zilberman, Yaron; Zilberman, Yaron; Zilberman, Yaron; Walken, Christopher, 1943-; Keener, Catherine; Hoffman, Philip Seymour, 1967-2014; Shawn, Wallace; Ivanir, Mark (20th Century Fox Home Entertainment, 2013)
A powerful story that blends raw emotion with fiery passion to form an unforgettable cinematic masterpiece. After 25 years together, the members of a world-renowned string quartet learn that their beloved cellist may soon be forced to retire. But the news stirs up equally painful challenges when competing egos, harbored resentment, and irrepressible lust threaten to derail the group as they struggle to maintain harmony in their music, and their lives.